Translation Solutions of Game Localization: Exclamative Utterances in The Genshin Impact Video Game - Oktaviana, Bunga Sully; Ishlahiyah, Mazroatul (Universitas Pendidikan Ganesha, 2024)
The burgeoning video game industry, localization has become a pivotal aspect of tapping into the global market. The rapid expansion of localization often leads to translators misinterpreting the storyline context within video games. This research aimed to analyze the typology and translation strategies used by translators to localize exclamative utterances in the video game Genshin Impact from English to Indonesia. This research employed a qualitative methodology with content analysis and document observation used as the approach. The study utilized Pym’s typology theory and Mangiron and O’Hagan’s translation strategies. The researchers collected 115 exclamative utterances from the video game Genshin Impact. The researchers found that translators only used six types of translation solutions to localize exclamative utterances including copying words, copying structure, perspective change, compensation, cultural correspondence, and text tailoring. Furthermore, the researchers also found that the translators only used three translation strategies in localized the exclamative utterances from English to Indonesian in the game Genshin Impact: proper names, culture-bound phenomena, and linguistic variation. The results showed that the translators demonstrated an understanding of the target language's culture that follows syntactic structures, language styles, and common expressions familiar to players. Future research is encouraged to develop further research on localization practices across different gaming genres to deepen the understanding of video game localization.